2016
DOI: 10.4303/jdar/235984
|View full text |Cite
|
Sign up to set email alerts
|

CART Peptides and Drugs of Abuse: A Review of Recent Progress

Abstract: Earlier studies suggesting an involvement of cocaine and amphetamine regulated transcript peptide (CARTp) in the actions of drugs of abuse are confirmed in the most recent publications. This seems especially true for the psychostimulants where CARTp in the nucleus accumbens inhibits or regulates the actions of these drugs; the regulation is lost after repeated drug use which may be an important mechanism in addiction. The other drugs, including nicotine, alcohol, opiates, and perhaps caffeine can affect CARTp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Previous work in the NAc indicated that CART peptide had an average inhibitory effect, and that this inhibition tended to regulate the maximal activity of the PS- or DA-induced behavioral effects; for reviews see (Rogge et al, 2008; Zhang et al, 2012; Subhedar et al, 2014; Kuhar, 2016). But in this study, we considered and included the individual responses in the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work in the NAc indicated that CART peptide had an average inhibitory effect, and that this inhibition tended to regulate the maximal activity of the PS- or DA-induced behavioral effects; for reviews see (Rogge et al, 2008; Zhang et al, 2012; Subhedar et al, 2014; Kuhar, 2016). But in this study, we considered and included the individual responses in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Cocaine-and-Amphetamine-Regulated-Transcript peptide (CART 55-102, CART peptide) is an active substance/neurotransmitter with a variety of effects throughout the body (Rogge et al, 2008; Zhang et al, 2012; Subhedar et al, 2014; Kuhar, 2016). In the brain, CART mRNA and peptides are found in many discrete nuclei including the nucleus accumbens (NAc), a region with a strong dopamine (DA) input (Douglass et al, 1995; Koylu et al, 1998), and exposure to cocaine (COC) or amphetamine (AMPH) increases the levels of CART mRNA in the NAc (Douglass et al, 1995; Albertson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include feeding and body weight, depression and anxiety, stress, hormonal control, psychostimulant (PS) action [2,3,4,5,6,7,8], and others. With regard to PS action, CART peptides appear to regulate the action of cocaine, amphetamine, and dopamine.…”
mentioning
confidence: 99%
“…With regard to PS action, CART peptides appear to regulate the action of cocaine, amphetamine, and dopamine. Injection of CART peptide (CART55-102) into the nucleus accumbens (NAc) reduces the average effect of PSs on locomotor activity (LMA) and cocaine-induced reward [2,3,4,5,6,7,8,9]. …”
mentioning
confidence: 99%